Surface characteristics and clogging of the contributing basin of La Esperanza reservoir, Manabí, Ecuador (Revista Científica Ciencias Naturales y Ambientales, 2023)
The aim of this research was to determine the current surface characteristic that has a major influence on the clogging of La Esperanza reservoir, in the province of Manabí, coastal Ecuador. The basin under study was delimited and physiographically characterized, through the use of Geographic Information Systems (GIS), through a digital elevation model (DEM) downloaded from the ALOS PALSAR satellite (https://www.asf.alaska.edu/), and complemented with the National Information System (www.sni.gob.ec). A greater geomorphology of regular slopes (32.13%) and highly dissected mesas (32.42%) with a sedimentary-type geology between tuffaceous sandstones, shales and siltstones prone to water erosion was determined. In conclusion, the Membrillo and Bejuco micro-basins in their upper part present gorges of canyoned valleys with slopes that reach 30 degrees, which together with precipitation becomes the main surface characteristic that has currently influenced greater clogging two of the branches of the reservoir.
Keywords: Reservoir; Clogging; Geomorphology; Cross sections